If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15c = 8c + 7 Reorder the terms: 15c = 7 + 8c Solving 15c = 7 + 8c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8c' to each side of the equation. 15c + -8c = 7 + 8c + -8c Combine like terms: 15c + -8c = 7c 7c = 7 + 8c + -8c Combine like terms: 8c + -8c = 0 7c = 7 + 0 7c = 7 Divide each side by '7'. c = 1 Simplifying c = 1
| (6x+5)(3x+2)(x+1)=28 | | a*4+b*7=60 | | A=(4m+h) | | a=(am+h) | | 5=-6+a | | 14.6=10.2 | | -8=2+k | | -a+9-6a=12-7a-3 | | 5x-10+9x+18=2x+2+2x-2 | | -6=c/7 | | 5x-10+9x+18=2 | | 5x=2x+22.5-27 | | 3x^2+10x-27=0 | | w^2-3w-40=0 | | -(15-12x)-(3x-15)(5x+22)=-12x(x-45)-(3x^2-400)-604 | | -3x^2+6x-3= | | 3x^3+3x^2+3x=0 | | 4-(x-2)=8-2x | | 3x-2=-2x+18 | | 200+(234+5000)2846= | | x^6+3x^3+1=y^4 | | ln(5x-3)-ln(10x+7)=0 | | z^2-(2i+1)z+i-1=0 | | p^3-6p+6=0 | | 65x=698555 | | (9x-4)(2x-6)+(7x-3)(x+5)-(5x+3)(5x+1)=4 | | 42x^2+20-36=4 | | -m/8-=5/8 | | 5log(x)+2=0 | | 8x-x+19=75 | | 0.91=(0.6-x)+2x | | (0.6-x)+2x=0.91 |